2018
DOI: 10.1590/s0004-2803.201800000-84
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Enteroaggregative Escherichia Coli Among Diarrheal Childrenin Western Brazilian Amazon

Abstract: BACKGROUND: Enteroaggregative Escherichia coli (EAEC) is one of the main acute and chronic diarrhea causes both in children and adults, mainly in developing countries. OBJECTIVE: The aim of the present study is to characterize EAEC strains isolated from faecal samples and to identify genes potentially contributing to virulence, biofilm production and antimicrobial resistance in children admitted to a pediatric hospital in Porto Velho, Rondônia State. METHODS: The total of 1,625 E. coli specimens were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Several of the virulence factor-encoding genes investigated here were statistically more frequent among typical EAEC, which is not surprising since the majority of these genes were identified, and functionally characterized, in the typical EAEC prototype strain 042 (Harrington et al, 2006;Chaudhuri et al, 2010;Hebbelstrup Jensen et al, 2014). Similar findings were also observed by other Brazilian authors that compared typical and atypical EAEC isolates, especially with the pic, aap, shf, and agg4A genes being more frequent among the typical EAEC isolates (Andrade et al, 2017;Taborda et al, 2018;Guerrieri et al, 2019). Case-control studies, performed in distinct geographic regions, have been able to demonstrate the association of some genes encoding virulence factors with diarrheal disease.…”
Section: Discussionsupporting
confidence: 89%
“…Several of the virulence factor-encoding genes investigated here were statistically more frequent among typical EAEC, which is not surprising since the majority of these genes were identified, and functionally characterized, in the typical EAEC prototype strain 042 (Harrington et al, 2006;Chaudhuri et al, 2010;Hebbelstrup Jensen et al, 2014). Similar findings were also observed by other Brazilian authors that compared typical and atypical EAEC isolates, especially with the pic, aap, shf, and agg4A genes being more frequent among the typical EAEC isolates (Andrade et al, 2017;Taborda et al, 2018;Guerrieri et al, 2019). Case-control studies, performed in distinct geographic regions, have been able to demonstrate the association of some genes encoding virulence factors with diarrheal disease.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of the a-EAEC was surprisingly higher and significantly associated with diarrhea compared with t-EAEC and non-diarrheal EAEC isolates. The majority of the epidemiological studies have reported t-EAEC isolates as the predominant subtype of EAEC isolated associated with the disease (6,32,45,48), while other studies have not been able to associate t-EAEC (AggR-positive) with diarrhea (19,49,50). Therefore the association of aggR-positive strains and diarrhea is not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of association concerning the STs of such hybrid strains circulating in the country. Moreover, most of these reports on hybrid strains were restricted to São Paulo, a cosmopolitan city of the Southeast Brazilian region, and until now, all studies reporting E. coli infections in the Amazon Region were associated only with diarrheagenic infections [19][20][21][22]. Therefore, further studies are required to investigate the distribution and potential impact of these strains on the clinical outcomes of affected individuals.…”
Section: Introductionmentioning
confidence: 99%